The Effectiveness of Digital Banking Byond in Increasing Quality Service and Satisfaction Custamers at Bank Syariah Indonesia Pamekasan Branch - Amina, Sitti; Hanifah, Luluk (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the implementation, effectiveness, and influence of BYOND digital banking services on improving service quality and customer satisfaction at Bank Syariah Indonesia KC Pamekasan . Using a descriptive qualitative approach, data were collected through semi-structured interviews with customers and documentation from various relevant sources. The results show that BYOND implementation is supported by customer education strategies, digital promotions, and strengthening frontline services, but faces digital literacy challenges for some customers. Service effectiveness is reflected in increased transaction speed and system reliability, despite being disrupted by a server downtime incident in 2023. Customer satisfaction generally increases due to ease of access, security, and speed of service, accompanied by a positive impact on corporate image and compliance with sharia principles. This study recommends improving digital literacy, strengthening technological infrastructure, and optimizing communication during disruptions to maintain service quality and customer satisfaction.